Brainstorm-DUNEuro: An integrated and user-friendly Finite Element Method for modeling electromagnetic brain activity - Medani, Takfarinas; Garcia-Prieto, Juan; Tadel, Francois; Antonakakis, Marios; Erdbrügger, Tim; Höltershinken, Malte; Mead, Wayne; Schrader, Sophie; Joshi, Anand; Engwer, Christian; Wolters, Carsten H.; Mosher, John C.; et al. (NeuroImage (Orlando, Fla.), 2023)
•Full FEM pipeline for electrophysiology (e-phys) forward modeling is proposed and integrated into brainstorm.•Realistic FEM mesh head models can be generated from the MR data (T1w /and T2w).•Realistic conductivity tensors can be generated from DWI and mapped to the FEM mesh.•E-phys FEM forward modeling can be performed either from an easy-to-use GUI or scripting using the DUNEuro solver.•Full anatomical data (MRI/DWI) and functional data (EEG/MEG) are distributed for easy analysis replication. Human brain activity generates scalp potentials (electroencephalography – EEG), intracranial potentials (iEEG), and external magnetic fields (magnetoencephalography – MEG). These electrophysiology (e-phys) signals can often be measured simultaneously for research and clinical applications. The forward problem involves modeling these signals at their sensors for a given equivalent current dipole configuration within the brain. While earlier researchers modeled the head as a simple set of isotropic spheres, today's magnetic resonance imaging (MRI) data allow for a detailed anatomic description of brain structures and anisotropic characterization of tissue conductivities. We present a complete pipeline, integrated into the Brainstorm software, that allows users to automatically generate an individual and accurate head model based on the subject's MRI and calculate the electromagnetic forward solution using the finite element method (FEM). The head model generation is performed by integrating the latest tools for MRI segmentation and FEM mesh generation. The final head model comprises the five main compartments: white-matter, gray-matter, CSF, skull, and scalp. The anisotropic brain conductivity model is based on the effective medium approach (EMA), which estimates anisotropic conductivity tensors from diffusion-weighted imaging (DWI) data. The FEM electromagnetic forward solution is obtained through the DUNEuro library, integrated into Brainstorm, and accessible with either a user-friendly graphical interface or scripting. With tutorials and example data sets available in an open-source format on the Brainstorm website, this integrated pipeline provides access to advanced FEM tools for electromagnetic modeling to a broader neuroscience community. [Display omitted]